Downstream effects of mutations in SOD1 and TARDBP converge on ene expression impairment in patient-derived motor neurons - Dash, Banaja Priyadarshini; Freischmidt, Axel; Weishaupt, Jochen H.; Hermann, Andreas (International journal of molecular sciences, 2022)
Amyotrophic Lateral Sclerosis (ALS) is a progressive and fatal neurodegenerative disease marked by death of motor neurons (MNs) present in the spinal cord, brain stem and motor cortex. Despite extensive research, the reason for neurodegeneration is still not understood. To generate novel hypotheses of putative underlying molecular mechanisms, we used human induced pluripotent stem cell (hiPSCs)-derived motor neurons (MNs) from SOD1- and TARDBP (TDP-43 protein)-mutant-ALS patients and healthy controls to perform high-throughput RNA-sequencing (RNA-Seq). An integrated bioinformatics approach was employed to identify differentially expressed genes (DEGs) and key pathways underlying these familial forms of the disease (fALS). In TDP43-ALS, we found dysregulation of transcripts encoding components of the transcriptional machinery and transcripts involved in splicing regulation were particularly affected. In contrast, less is known about the role of SOD1 in RNA metabolism in motor neurons. Here, we found that many transcripts relevant for mitochondrial function were specifically altered in SOD1-ALS, indicating that transcriptional signatures and expression patterns can vary significantly depending on the causal gene that is mutated. Surprisingly, however, we identified a clear downregulation of genes involved in protein translation in SOD1-ALS suggesting that ALS-causing SOD1 mutations shift cellular RNA abundance profiles to cause neural dysfunction. Altogether, we provided here an extensive profiling of mRNA expression in two ALS models at the cellular level, corroborating the major role of RNA metabolism and gene expression as a common pathomechanism in ALS.
Gesehen am 26.10.2022